Improving Pancasila and Citizenship Education Based on Android Digital Pocket Book for Grade VIII Students - Ridho ApriliaNugraha; Zuwirna Zuwirna; Zelhendri Zen; Rayendra Rayendra (STAI Hubbulwathan Duri, 2025)
The integration of digital media in education is crucial for enhancing student engagement and learning outcomes. At SMP Negeri 14 Kerinci, outdated printed teaching materials that do not align with the current syllabus contribute to low student performance. To address this issue, this study develops and evaluates an Android-based digital pocket book for Pancasila Citizenship Education. The research follows the Research and Development (RD) approach using the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. Validation was conducted by three experts specializing in media, materials, and language, assessing the application based on relevance, interactivity, language quality, and content. Practicality testing involved teachers and students, and effectiveness was determined through pretest-posttest comparisons. Validation results indicated high feasibility, with scores of 82 for media, 82 for materials, and 85 for language, all classified as “Very Good.” Practicality testing yielded scores of 98 from teachers and 96 from students, categorizing the application as “Very Practical.” Effectiveness analysis demonstrated significant improvements in student learning outcomes, as evidenced by pretest and posttest score differences and the achievement of classical completeness. The findings confirm that the digital pocket book is a viable and effective learning tool, enhancing students' understanding and engagement through multimedia features such as audio, video, images, and animations. This study provides an innovative digital learning solution with the potential to serve as a model for other educational subjects, contributing to the advancement of digital-based pedagogy.